Towards a unified view of Islamic education - Halstead, J. Mark (Islam and Christian-Muslim relations, 1995)
The paper attempts to sketch an Islamic view of education in line with fundamental Islamic beliefs and values. This view is presented first in strictly Islamic terms, but then in response to a liberal critique of the Islamic view, it is re-expressed in terms which are more accessible to Western liberals and which thus, it is hoped, make continuing dialogue about education possible.